Channel changes of the Adige River (Eastern Italian Alps) over the last 1000 years and identification of the historical fluvial corridor. Issue 2 (13th November 2018) - Scorpio, Vittoria; Surian, Nicola; Cucato, Maurizio; Dai Prá, Elena; Zolezzi, Guido; Comiti, Francesco
ABSTRACT: A 1:50, 000-scale geomorphological map of the Adige/Etsch River valley bottom (NE Italy) is presented. The study area is 115 km long, and it extends between the villages of Merano/Meran and Calliano, including also the terminal segments of 9 major tributaries of the Adige River. Presently, the Adige shows a sinuous to straight morphology owing to massive channelization occurred during the nineteenth century. Fluvial geomorphological features have been mapped through a detailed-scale comparative multi-temporal analysis carried out on several historical maps dating since the eighteenth century, previous thematic maps, geological maps of the Italian 'CARG' project, orthophotos (2011) and high – resolution DEMs. The map shows the active river channel, dating to 1803–1805 (before channelization), to 1856-1861 (during channelization) and under present conditions, as well as several paleo-channels dating up to the thirteenth century. The analysis led to define the corridor of historical channel changes, a fundamental tool for river management purposes.